Systematic Assessment of Exposure Variations on Observed Bioactivity in Zebrafish Chemical Screening - Wilson, Lindsay B. (Toxics, 2020)
The embryonic zebrafish is a powerful tool for high-throughput screening of chemicals. While this model has significant potential for use in safety assessments and chemical prioritization, a lack of exposure protocol harmonized across laboratories has limited full model adoption. To assess the potential that exposure protocols alter chemical bioactivity, we screened a set of eight chemicals and one 2D nanomaterial across four different regimens: (1) the current Tanguay laboratory’s standard protocol of dechorionated embryos and static exposure in darkness; (2) exposure with chorion intact; (3) exposure under a 14 h light: 10 h dark cycle; and (4) exposure with daily chemical renewal. The latter three regimens altered the concentrations, resulting in bioactivity of the test agents compared to that observed with the Tanguay laboratory’s standard regimen, though not directionally the same for each chemical. The results of this study indicate that with the exception for the 2D nanomaterial, the screening design did not change the conclusion regarding chemical bioactivity, just the nominal concentrations producing the observed activity. Since the goal of tier one chemical screening often is to differentiate active from non-active chemicals, researchers could consider the trade-offs regarding cost, labor, and sensitivity in their study design without altering hit rates. Taken further, these results suggest that it is reasonably feasible to reach agreement on a standardized exposure regiment, which will promote data sharing without sacrificing data content.